Factors Influencing Mothers' Participation in Visiting Integrated Health Posts for Infants and Toddlers - Siti Sarifah; Dianna Dianna; Dessy Hidayati Fajrin (MEDICA (International Medical Scientific Journal), 2026)
Infant and toddler health services at integrated health posts (posyandu) play a crucial role in disease prevention and the improvement of child health through routine monitoring, which requires active maternal participation. Mothers’ participation is a key determinant of the effectiveness of these services. This study aimed to identify factors influencing mothers’ participation in posyandu visits for infants and toddlers in the working area of the Pahauman Community Health Center. This study employed an analytical survey design with a cross-sectional approach. The population consisted of all mothers with children aged 12–59 months, totaling 1,437 individuals. A sample of 65 respondents was selected using stratified random sampling. Data were analyzed using univariate and bivariate analyses. The univariate results showed that most respondents had good knowledge, lived close to the health center, and had access to complete posyandu facilities, although family support was relatively low. The majority of mothers demonstrated active participation in posyandu visits. Bivariate analysis revealed significant relationships between knowledge, distance from home, and family support with mothers’ participation in posyandu visits. In conclusion, mothers’ knowledge, proximity to health facilities, and family support are important factors influencing participation in posyandu visits. Strengthening these factors is essential to improve maternal involvement and optimize child health services.